Endovascular thrombectomy versus intravenous tissue plasminogen activator for vertebrobasilar stroke treatment: insights from the national inpatient sample - Ram Saha; Gaurav Nepal; Dhanshree Solanki; Ahmed Shaheen; Mohammed Maan Al-Salihi; Shamser Singh Dalal; Anil Roy (Frontiers in Neurology)
IntroductionApproximately 20% of patients, who present with acute ischemic stroke are diagnosed with acute vertebrobasilar artery occlusion (VBAO), which is caused by an embolus or ruptured atherosclerotic plaque leading to the formation of an acute thrombus. The mortality rate of VBAO is extremely high without treatment, ranging from 80 to 95%, underscoring the urgent need for effective and timely treatment strategies. In this study, we examined the trends of hospitalizations for Endovascular Thrombectomy (EVT) or intravenous tissue plasminogen activator (IV-tPA) as interventions for VBAO, their outcomes, associated complications, and predictors of mortality in patients undergoing these procedures.MethodsWe utilized the National Inpatient Sample (NIS) database to extract data from the years 2016 to 2018, using ICD-10 diagnosis and procedure codes specific to occlusion or thrombosis of the vertebral artery or basilar artery, IV-tPA, and EVT.ResultsBetween 2016 and 2018, a total of 37,310 patients were admitted with VBAO. Among these, tPA was administered in 2,530 admissions (6.8%), while EVT was performed in 2,330 admissions (6.2%). IV-tPA was more frequently used in the age groups of 65–84 years and, ≥85 years, whereas EVT was more commonly used in the age groups of 18–44 years and 45–64 years. There was no significant difference in usage between men and women. In large hospitals, EVT was more commonly used than IV-tPA (8.1% vs. 7%, p < 0.0001), while in small hospitals, IV-tPA usage was significantly higher (3.8% vs. 2%, p < 0.0001). The all-cause mortality rate was significantly higher in EVT admissions compared to IV-tPA admissions (16.8% vs. 8.1%, p < 0.0001). However, there was no significant difference in the mean length of stay (LOS) between the two modalities.ConclusionA trend of higher rates of EVT was observed in the younger age group (18–64 years) compared to the older age group, but no significant difference was noted based on sex. The all-cause mortality rate was found to be higher in the EVT group compared to the IV-tPA group. However, there was no significant difference in the length of hospital stay between the two groups.